Pengaruh Pembelajaran Berbasis Keteladanan dan Kecerdasan Emosional Terhadap Sikap Hormat Siswa Kepada Guru di MI Miftahul Ulum - Iffatul Afifah Afifah; Hani Nafi'ah Rachmawati Hani; Lyke Nuroniyah Lailatul Luthfi Lyke; Muhammad Alfi Syahrin Alfin (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to analyze the influence of exemplary-based learning and emotional intelligence on students’ respectful attitudes toward teachers at MI Miftahul Ulum. This research employed a correlational quantitative approach, involving a sample of 60 fourth- and fifth-grade students selected through a simple random sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of SPSS 16. The results showed that exemplary-based learning had a positive and significant effect on students’ respectful attitudes, with a significance value of 0.030. Emotional intelligence also had a positive and significant effect, with a significance value of 0.006. Simultaneously, both variables had a significant effect on students’ respectful attitudes toward teachers, with a significance value of 0.000 and an R Square value of 0.423, indicating that both variables explained 42.3% of the variance in students’ respectful attitudes. These findings affirm that students’ respectful attitudes are not shaped merely by school rules, but also through teachers’ living examples and students’ well-directed emotional intelligence. Teachers who are consistent, polite, fair, and empathetic serve as moral mirrors that cultivate manners in a more meaningful way.